Comparative evaluation of implant stability using bone expanders and conventional osteotomy - Geo Pius; SK Saranya; Aswini Kumar; Anil Mathew; Chandrashekar Janakiram; Siddarammana G. Gowd; Parvathy Balachandran (Elsevier, 2022)
Aim: The purpose of this study was to compare the implant stability and bone implant contact obtained using bone expanders to conventional osteotomy. Materials and methods: In this multiphasic study, the first phase was conducted on ex vivo porcine models to standardize the procedure and to check its feasibility. The second phase was conducted as human clinical trial. Phase I: A total of 10 implants were placed in the premolar region on five exvivo porcine models in randomized sequence using conventional osteotomy drills and bone expanders/screw spreaders. Implant stability was measured using resonance frequency analyser on the day of implant placement. Radiological analysis was done using micro-CT in two sectional block specimens randomly selected from each study groups. Phase II: Implants were placed on ten patients fulfilling the inclusion criteria. Implants were placed after randomizing the osteotomy sites. Bone expanders were used in 5 sites and conventional osteotomy technique was used in 5 other sites. Implant stability was measured on the day of implant placement and after three months in pre-loaded state using resonance frequency analyser. Results: Phase I: Average implant stability quotient for bone expanders were 71.2% ± 3.8% and 66.4% ± 1.3% for conventional osteotomy respectively. Bone to implant contact ratio values for bone expanders were 84.7% ± 7.9% and conventional osteotomy drills were 66.3% ± 13.6%. Phase II: Average primary stability at the day of surgery was 71.4 ± 1.3 for bone expanders and 65.6 ± 2.4 for conventional osteotomy drills. After three months (per-loaded state), average primary stability of bone expanders were 74.8 ± 1.1 and conventional osteotomy drills were 71.8 ± 2.5. Conclusion: The bone expanders used when indicated can enhance implant stability and bone to implant contact. Thus osteotomy by bone expanders may be suggested as a promising method especially in compromised bone.